The potential of agroforestry to reduce atmospheric greenhouse gases in Canada: Insight from pairwise comparisons with traditional agriculture, data gaps and future research - Mark Baah-Acheamfour; Scott X. Chang; Edward W. Bork; Cameron N. Carlyle (The Forestry Chronicle)
Canadian agriculture is a source of greenhouse gases (GHG) and agroforestry has the potential to sequester carbon (C), and mitigate agricultural GHG emissions. Agroforestry systems are common features in Canada’s agricultural landscape; however, there are limited empirical data to support implementation of agroforestry practices for GHG mitigation. This shortfall of data may be a contributing factor to the lack of policy that supports the use of agroforestry for GHG mitigation in the Canadian agricultural landscape. We reviewed published studies that compared C stocks in vegetation and soils, and/or GHG emissions in agroforestry systems to traditional agriculture across Canada, with the aims of assessing the benefit of adopting agroforestry for GHG reduction. We then identified data gaps and obstacles that could direct future research. We found that most studies reported increases in vegetation and soil organic C storage in areas with woody species compared to herbaceous crops. Agroforestry systems also reduced the emission of CH4 and N2O, and increased CO2 respiration from soil, but few studies have examined these gases. The small set of studies we reviewed demonstrated the potential of agroforestry to store terrestrial C and mitigate GHG emissions. However, additional research is required to verify this pattern across geographic regions, determine the regional potential for development of agroforestry systems, and assess the potential atmospheric GHG reduction at regional and national scales.